P PREDIKSI PERTUMBUHAN EKONOMI KOTA MALANG DENGAN MODEL ARIMA - mochamad, husni (Teknologi Informasi : Teori, Konsep, dan Implementasi : Jurnal Ilmiah, 2024)
This research aims to apply data mining methods with the ARIMA model to predict the rate of economic growth in Malang City by using techniques in data mining to obtain varied and long-term predictions. The problem arises due to the use of conventional methods that are less able to provide projections for economic growth in the next few years. To overcome this problem, research using the ARIMA model is expected to solve the problem by producing predictions for the next few years and a good level of accuracy. The data used in this study were obtained from the Central Bureau of Statistics and Malang City Government for the period 2004 to 2023. The ARIMA (0,0,1) model is used as the main model in predicting the economic growth rate in Malang City along with five variables that may have an influence on the main variable. The ARIMA (0,0,1) model has a better level of accuracy when compared to the ARIMA (1,0,1) and ARIMA (1,1,1) models. The results showed that the ARIMA model built was able to predict the rate of economic growth quite well. This study concludes that the ARIMA model created is more varied in predicting economic growth and needs to be used parameters or methods, so that the prediction results can be used as a reference for the government in planning a more effective and efficient economic development strategy